Adaptation to climate variability and change in Uganda: Are there gender differences across households? - Madina Guloba (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
This paper hypothesizes that adaptation to climate change is influenced by the gender of the decision maker of the household. Using a two-wave household panel survey dataset, choice of adaptation strategies employed by female- and male-headed households are examined. A multinomial logit model is used to examine factors determining adaptation choices by gender. Findings reveal that gender of the household head matters in adaptation to climate-induced shocks. Specific differences were found regarding responses during drought, regarding crop pest attacks, and livestock epidemics. Agro-ecological climate zones in which households live play a key role in adaptation options, yet gender matters.
Keywords: C35; J16; Q54; 330; adaptation; climate change; covariate shocks; gender; multinomial logit